A platform for chemical modification of mandelate racemase: characterization of the C92S/C264S and γ-thialysine 166 variants. Issue 4 (30th May 2018) - Nagar, Mitesh; Kumar, Himank; Bearne, Stephen L
Abstract: Mandelate racemase (MR) serves as a paradigm for our understanding of enzyme-catalyzed deprotonation of a carbon acid substrate. To facilitate structure–function studies on MR using non-natural amino acid substitutions, we engineered the Cys92Ser/Cys264Ser variant (dmMR) as a platform for introducing Cys residues at specific locations for subsequent covalent modification. While the highly reactive thiol of Cys furnishes a site for chemical modification, site-specificity requires that other Cys residues be non-reactive or replaced by a non-reactive amino acid, especially if chemical modification is conducted under denaturing conditions. The catalytic efficiency of dmMR is reduced only 2-fold relative to wild-type MR, making dmMR a viable platform for the site-specific introduction of Cys. As an example, the inactive Lys166Cys variant of dmMR was treated with ethylenimine under denaturing conditions to replace the Brønsted acid-base catalyst Lys 166 with the non-natural amino acid γ-thialysine. Comparison of the pH-activity profiles of dmMR and the active γ-thialysine variant revealed a reduction in the p K a for the side chain amino group of 0.4 units for the latter variant. Unlike wild-type MR for which diffusion is partially rate-limiting, dmMR and the γ-thialysine variant showed no dependence on the solvent viscosity suggesting that the chemical step is fully rate-limiting.